The Continuous Clock: A Working Academic Mother during COVID-19 - Hicks-Roof, Kristen (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
My vision for maternity leave was quickly flipped upside down, as I had our second daughter on March 13, 2020. Amid the most significant pandemic of my lifetime, I was not prepared for what was to come over the next several months and how it would change the trajectory of my career. As a fulltime faculty member at a university, I am heavily involved in both teaching and research. During my maternity leave, I was planning to be home with my newborn for a few months while sending my older daughter to daycare. This bonding and recovery time are critical for both mom and baby. However, as universities closed, I no longer had the assistance needed to facilitate my research, nor did I have childcare. That burden was now placed back on my shoulders soon after delivery. COVID-19 has had significant effects on both the plans and expectations of mothers in academia. This piece will touch on societal expectations of mothers as well as the discrimination they have faced in academia during this crisis. I will tell a personal story as well as share stories from my peers about women’s (and men’s) roles and responsibilities for the family, while managing expectations as university faculty members. Four themes emerged from the qualitative interviews: productivity vs. efficiency, opportunity vs. challenge, collaborative parenting vs. parenting alone, and the repercussions from COVID-19 and responses to them. It is an important time to describe the personal and professional setbacks academic mothers have faced because of this pandemic.